Three new species of Afropselaphus Jeannel, 1950 (Staphylinidae: Pselaphinae) from Greece and a redescription of Pselaphogenius treskanus (Karaman, 1940) - Davranoglou, Leonidas-Romanos; Baňař, Petr; Kakiopoulos, George; Balázs, Attila; Avtzis, Dimitrios N.; Hlaváč, Peter (Zootaxa, 2023)
Three new species of the genus Afropselaphus Jeannel, 1950, Afropselaphus taygetensis sp. n., Afropselaphus tymficus sp. n. and Afropselaphus euboicus sp. n. are described and illustrated. Pselaphogenius treskanus (Karaman, 1940) is redescribed and new data of its distribution are provided.